Increased Screen Time Is Associated With Alcohol Desire and Sweetened Foods Consumption During the COVID-19 Pandemic - Tebar, William R.; Christofaro, Diego G. D.; Diniz, Tiego A.; Lofrano-Prado, Mara Cristina; Botero, Joao Paulo; Correia, Marilia de Almeida; Cucato, Gabriel G.; Ritti-Dias, Raphael Mendes; Prado, Wagner Luiz do (Frontiers in Nutrition, 2021)
Background: Elevated screen time has been associated with alcohol and sugar intake and smoking previously pandemic. Considering substantial screen time increase caused by social isolation during COVID-19 pandemic, this study aimed to analyze the association of increased time in different screen devices with consumption and increased desire of alcohol, smoking, and sweetened foods in adults. Methods: A sample of 1897 adults (58% of women) with mean age of 37.9 (13.3) years was assessed. Participants were asked whether screen time in television, cell phone, and computer increased during pandemic. Closed questions assessed consumption of alcohol and sweetened foods and smoking, as their increased desire during pandemic. Educational level, age, sex, feeling of stress, anxiety, and depression, and screen use for physical activity were covariates. Results: Increased television time was associated with increased desire to drink (OR=1.46, 95%CI: 1.12-1.89) and increased sweetened foods consumption (OR=1.53, 95%CI: 1.18-1.99), while increased computer time was associated with lower consumption of alcohol (OR=0.68, 95%CI: 0.53-0.86) and sweetened foods (OR=0.78, 95%CI: 0.62-0.98). Increased cellphone time was associated with increased sweetened foods consumption (OR=1.78, 95%CI: 1.18-2.67). Participants with increased time in three devices were less likely to consume sweetened foods for ≥5 days/week (OR=0.63, 95%CI: 0.39-0.99), but were twice as likely to have sweetened foods consumption increased (OR=2.04, 95%CI: 1.07-3.88). Conclusion: Screen time was differently associated with consumption and desire for alcohol and sweets according to screen devices. Increased time in television and cellphone needs to be considered for further investigations of behavioral impairments caused by pandemic.